Differential effects of habitat loss on occupancy patterns of the eastern green lizard Lacerta viridis at the core and periphery of its distribution range - Prieto-Ramirez, Ana María; Röhler, Leonie; Cord, Anna F; Pe'er, Guy; Rödder, Dennis; Henle, Klaus (PloS one, 2020)
The effects of habitat loss on the distribution of populations are often linked with species specialization degree. Specialist species can be more affected by changes in landscape structure and local patch characteristics compared to generalist species. Moreover, the spatial scale at which different land covers (eg. habitat, cropland, urban areas) affect specialist species can be smaller. Specialization is usually assumed as a constant trait along the distribution range of species. However, for several taxa, there is evidence of higher specialization degree in peripheral populations compared with populations in the core. Hence, peripheral populations should have a higher sensitivity to habitat loss, and strongest effects should be found at a smaller spatial scale. To test these expectations, we implemented a patch-landscape approach at different spatial scales, and compared effects of landscape structure and patch characteristics on occupancy probability among northern peripheral, more specialized populations (Czech Republic) and core populations (Bulgaria) of the eastern green lizard Lacerta viridis. We found that landscape structure and patch characteristics affect differently the occupancy probability of Lacerta viridis in each region. Strongest effects of habitat loss were found at a spatial scale of 150m around patches in the periphery, but at a scale of 500m in the core. In the periphery occupancy probability of populations was principally affected by landscape composition, and the effect of habitat quality was stronger compared to core populations. In the core, persistence of populations was mainly explained by characteristics of the spatial configuration of habitat patches. We discuss possible ecological mechanisms behind the relationship between sensitivity to habitat loss, populations' specialization degree and position in the distribution range, and suggest conservation measures for L. viridis.
Keywords: pravděpodobnost; Bulgaria; Lizards; Bulharsko; ekologie; Animals; Ecology; Česká republika; Czech Republic; zvířata; ještěři; Probability; ekosystém; Ecosystem